SUPPLIER SELECTION USING AHP-TOPSIS: CASE STUDY IN TAIGERSPRUNG RESTAURANT - Tjindana, Bevin Ottismalleo; fitriani, katlea; Irawan, Yeremias Budi (Bina Ekonomi, 2024)
The Taigersprung restaurant in Yogyakarta, operating in the food and beverage industry, plans to expand after two years of establishment. To meet the needs of the new branch, the restaurant needs to increase production but faces obstacles such as fluctuating raw material prices and issues with shrimp suppliers that do not meet quality standards. The restaurant aims to add shrimp suppliers by evaluating several potential ones. The lack of a structured supplier evaluation method makes choosing the best supplier challenging for the restaurant. This research aims to identify criteria for selecting shrimp suppliers and finding the best one. Through interviews with the restaurant owner and literature studies, the research utilizes the Analytical Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The research results indicate that quality criteria are the top priority in selecting shrimp suppliers, followed by price, delivery, service, and flexibility. Based on TOPSIS calculations, supplier B becomes the restaurant's top priority for collaboration.